Influence of chain length of long-chain fatty acid surfactant on the thermal conductivity of magnetite nanofluids in a magnetic field - Dadwal, Arun; Dadwal, Arun (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2018)
Stable magnetic nanofluids are prepared by dispersing long-chain fatty acid surfactants coated magnetite (Fe3O4) nanoparticles in toluene and investigated the effect of chain length of the surfactant molecules on the thermal conductivity of the magnetite nanofluids in a magnetic field. Superparamagnetic magnetite nanoparticles having a comparable particle size (similar to 10 nm) are coated with three different long-chain fatty acid surfactants; myristic acid (C13H27COOH), palmitic acid (C15H31COOH) and stearic acid (C17H35COOH). The thermal conductivity of the nanofluids, in a magnetic field, is found to decrease with increasing the chain length of the surfactant molecule. Among the three fluids, the shorter chain myristic acid coated nanofluid showed larger enhancement in the thermal conductivity at smaller fields as compared to the other fluids. The results indicated that the chain length of the surfactant molecule present on the surface of the magnetite nanoparticles affect the thermal conductivity of the magnetic nanofluid in an external magnetic field, due to the difference in the extent of interdigitation of the surfactant molecules.